2021
DOI: 10.1038/s41398-021-01541-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial prefrontal cortex/anterior cingulate cortex Glx, glutamate, and GABA levels in medication-free major depressive disorder

Abstract: Glutamate (Glu) and gamma-aminobutyric acid (GABA) are implicated in the pathophysiology of major depressive disorder (MDD). GABA levels or GABAergic interneuron numbers are generally low in MDD, potentially disinhibiting Glu release. It is unclear whether Glu release or turnover is increased in depression. Conversely, a meta-analysis of prefrontal proton magnetic resonance spectroscopy (1H MRS) studies in MDD finds low Glx (combination of glutamate and glutamine) in medicated MDD. We hypothesize that elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…However, a high field strength (7T) MRS study found no difference in anterior cortical glutamate levels between cases of MDD and healthy controls, although increased glutamatergic activity was detected in the pathways to the basal ganglia [ 55 ]. A recent MRS study of depression found that increased total glutamate/glutamine (Glx) corresponded to more severe or untreated MDD and was correlated with reductions in GABA levels [ 56 ]. This suggests that impaired GABA functioning plays a role in glutamate excitotoxicity-induced depression.…”
Section: Depressionmentioning
confidence: 99%
“…However, a high field strength (7T) MRS study found no difference in anterior cortical glutamate levels between cases of MDD and healthy controls, although increased glutamatergic activity was detected in the pathways to the basal ganglia [ 55 ]. A recent MRS study of depression found that increased total glutamate/glutamine (Glx) corresponded to more severe or untreated MDD and was correlated with reductions in GABA levels [ 56 ]. This suggests that impaired GABA functioning plays a role in glutamate excitotoxicity-induced depression.…”
Section: Depressionmentioning
confidence: 99%
“…Imbalance of inhibitory and excitatory neurotransmission in the PFC and hippocampus has been involved in depression and convergent evidence from clinical and preclinical studies indicates that dysfunction of glutamatergic and GABAergic systems may contribute the pathophysiology of MDD 44,56 . MDD is generally accompanied by low GABA levels or GABAergic interneuron numbers, possibly disinhibiting glutamate release 320 . Ketamine was reported to inhibit presynaptic NMDARs of GABAergic interneurons present in excitatory neurons within the hippocampus and/or mPFC regions, resulting in the release of tonic inhibition that subsequently leads to increased firing of pyramidal neurons, augmenting synaptic transmission, thus orchestrating quick‐acting antidepressant functions 44,313,314 .…”
Section: Pharmacological Profile Of Ketamine and Its Underlying Mecha...mentioning
confidence: 99%
“…44,56 MDD is generally accompanied by low GABA levels or GABAergic interneuron numbers, possibly disinhibiting glutamate release. 320 Ketamine was reported to inhibit presynaptic NMDARs of GABAergic interneurons present in excitatory neurons within the hippocampus and/or mPFC regions, resulting in the release of tonic inhibition that subsequently leads to increased firing of pyramidal neurons, augmenting synaptic transmission, thus orchestrating quick-acting antidepressant functions. 44,313,314 Importantly, the burst of glutamate is thought to occur via blockade of NMDARs on GABA interneurons, which are more sensitive to the openchannel blocking actions of ketamine.…”
Section: Underlying Molecular Signaling In the Rapid And Sustained An...mentioning
confidence: 99%
“…We combined the data from coil elements using unsuppressed water signal as a reference. 19,20 We removed the residual water signal using a singular value decomposition-based method [21][22][23] and performed spectral alignment among the 30 water-suppressed FIDs by aligning the second to the 30th FIDs to the first one, using a fitting procedure like that of Near et al, using the Lorentzian lineshape function. 24…”
Section: Data Preprocessingmentioning
confidence: 99%